Determinants of Adoption and Usage of ICT by Small and Medium Enterprises in Kenya: The Case of Kikuyu Sub-County in Kiambu County - Thuo, Stephen N.; Namusonge, Dr. Mary (European Journal of Business and Strategic Management, 2017)
Purpose: Small and medium-sized firms are helping to generate employment opportunities and creation of wealth in the economies that are developing and also the developed ones. However, SMEs appear to have lagged behind and are not as fast in adopting and using ICT. The purpose of this research was to investigate the influence of stakeholders' support on adoption and usage of ICT by SMEs, and to establish how training /skills of staff is a determinant of the usage and adoption of ICT by SMEs in Kiambu County. This study was carried out in the County of Kiambu, Kenya. Methodology: Descriptive research design was used in the study. To obtain primary data, a structured questionnaire was administered to the sampled population. A sample size of 153 CEOs/proprietors of SMEs was used in the study out of a target population of 1507 registered SMEs by Kikuyu Sub-county Authorities. Stratified sampling and simple random sampling were used to draw the sample-size from the study population. Descriptive statistics was used to analyze the obtained data. Findings: The data findings show that taking other independent variable to be constant, an increase of one unit of Stakeholders' support would cause a 0.877 increase in Adoption and usage of ICT by small and medium enterprises and a unit increase in training /skills of staff lead to a 0.705 increase in Adoption and usage of ICT by small and medium enterprises. Conclusion and policy recommendation: This concludes that Stakeholders' support contribute more to the usage and adoption of ICT by small and medium enterprises followed by training /skills of staff. Therefore, the study recommends that training programs for personnel at all levels of the SMEs in Kiambu County should be conducted to help them understand their responsibilities in adoption and usage of ICT.